Proof of Some Conjectures of Melham Using Ramanujan’s 1ψ1 Formula - Bipul Kumar Sarmah (International Journal of Mathematics and Mathematical Sciences)
We employ Ramanujan's  1ψ1 formula to prove three conjectures of R. S. Melham on representation of an integer n as sums of polygonal numbers.